Assessment of immunization coverage among under-five year old children residing in slum settlements in an urban area in coastal Karnataka - S Phadnis (Global Journal of Medicine and Public Health, 2015)
Background National Family Health Survey conducted in the year 2005-6 reported that only 43.5 % of under five year old children are fully immunized in India. Various studies have shown that coverage of immunization among under five year old children living in urban slums is lesser then the national average which makes them susceptible to the various vaccine preventable diseases. Objectives To ascertain the coverage of immunization and determinants of its uptake among under five year old children residing in slums of Udupi taluka, Karnataka. Material and Methods This study was conducted in the slum settlements of Udupi taluka in Udupi district of Karnataka state. A community based descriptive cross sectional study design was used in the present study. The total number of under five year old children studied was 267 and they were selected by convenience sampling. Information on immunization was obtained from mother, father or any other care giver of child with the help of a pretested semi-structured questionnaire. Data was analysed using SPSS version 15. Proportion of children who were immunized fully, partially or not immunized at all was calculated. Chi-square test was performed to ascertain the factors associated with uptake of immunization by the under five year old children. Results It was found that the proportion of under- five year age children that were immunized fully, partially & not immunized at all was 64.8%, 31.5% & 3.7% respectively. In bivariate analysis, family income(p=0.002), variables related to maternal health care like utilization of Thayi card(p=0.002), availing antenatal care(p=0.043) and postnatal care(p=<0.001), tetanus toxoid immunization status of the mother(p=0.034), mother’s participation in meeting conducted by AWW/ASHA(p=<0.001) along with place of delivery of the child(p=0.009) and birth order(p=0.048) was associated with immunization status of the children. Conclusions Immunization coverage amongst the under-five year old children living in slum settlements is low. Promoting utilization of maternal health care by the pregnant women residing in slum settlements has the potential to increase the coverage of childhood immunization amongst the children residing there.